A Bibliometric Analysis of Employer Branding in the Recruitment Process - Loso Judijanto; Yendri Deswin; Yuanis Yuanis; L. Happy Amira; Novi Vizainiyah (West Science Social and Humanities Studies, 2026)
This study conducts a bibliometric analysis of research on employer branding within the recruitment process to map its intellectual structure, thematic evolution, and global collaboration patterns. Data were retrieved from indexed scientific publications and analyzed using VOSviewer to examine co-occurrence networks, co-authorship structures, country collaborations, density visualization, and citation analysis. The findings reveal that employer branding serves as a central construct strongly associated with recruitment, employer attractiveness, and social media, highlighting its strategic role in talent acquisition processes. The intellectual foundation of the field is primarily shaped by seminal works such as Backhaus and Tikoo (2004), while contemporary studies extend the discourse toward digital transformation, artificial intelligence, and data-driven recruitment systems. Thematic analysis indicates that the literature is organized into several clusters, including recruitment strategies, organizational attractiveness, psychological theories (e.g., signaling theory and social identity theory), and technology-enabled hiring systems. Overlay and density visualizations further show a temporal shift from foundational HR branding concepts toward emerging themes such as AI, e-recruitment, and gamification.